2022
DOI: 10.1016/j.jmig.2021.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol for the Management of Endometriosis and Chronic Pelvic Pain

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…adjunct to pain and 13% of these reported the use of cannabis to control symptoms. In addition, it is noteworthy that the use of medicinal cannabis can be administered orally 31 .…”
Section: Treatment Of Endometriosis With Cannabidiol and Its Adverse ...mentioning
confidence: 99%
See 1 more Smart Citation
“…adjunct to pain and 13% of these reported the use of cannabis to control symptoms. In addition, it is noteworthy that the use of medicinal cannabis can be administered orally 31 .…”
Section: Treatment Of Endometriosis With Cannabidiol and Its Adverse ...mentioning
confidence: 99%
“…In contrast to the adverse events associated with the use of cannabis reported, 10% had effects such as drowsiness, increased anxiety or tachycardia, these being the most common. However, it was concluded that the potential benefits of cannabis may outweigh the harms and that long-term data are lacking 31 .…”
Section: Treatment Of Endometriosis With Cannabidiol and Its Adverse ...mentioning
confidence: 99%
“…Likewise, its participation in neurotransmission systems such as serotonergic, GABAergic and glutamatergic has the power to mitigate anxiety and decrease nausea [ 311 ]. Despite the facts, the lack of clinical evidence in patients with MDD or patients who have other particularities that could increase the risk of developing MDD in women (endometriosis or loss of quality of life in pregnancy) means that its use cannot be recommended [ 313 , 314 , 315 ]. It can be concluded that future research is necessary to discover the advantages that this nutraceutical provides in the particularities of the MDD pathology.…”
Section: Nutritional Intervention In Women With Mddmentioning
confidence: 99%
“…The expanding legalization of recreational cannabinoids has led to a recent surge in the use of cannabinoids as a form of self-management therapy for many diseases, including EMS (Carrubba et al 2021;Sinclair et al 2019). Several articles in the past have thoroughly discussed the use and effectiveness of cannabinoids for pain management in EMS patients and the broad role of ECS in reproductive disorders (Mistry et al 2022;Bouaziz et al 2017;Maia et al 2020). One of the recent meta-analyses conducted by Mistry et al reviewed the effects of cannabis-based products on female reproductive health in the context of EMS and chronic pelvic pain and suggested that fertility complications and long-term cognitive functions might be affected.…”
Section: Introductionmentioning
confidence: 99%
“…One of the recent meta-analyses conducted by Mistry et al reviewed the effects of cannabis-based products on female reproductive health in the context of EMS and chronic pelvic pain and suggested that fertility complications and long-term cognitive functions might be affected. Additionally, the authors also acknowledge the lack of thorough and reliable evidence to support or dismiss the use of cannabinoids to treat EMS symptoms (Mistry et al 2022). Similarly, a study conducted by Bouaziz et al in 2017 summarized the role of ECS in EMS-associated pain symptoms and the potential use of cannabinoids as therapeutic agents, where they concluded that pain mechanisms are heterogenous in EMS patients and the use of cannabinoids for the treatment of EMS needs to be evaluated carefully (Bouaziz et al 2017).…”
Section: Introductionmentioning
confidence: 99%